Recovering of Biodiversity in Bottomland Hardwood Forests After a Tornado and Salvage Logging in Southern Illinois (USA) - Laura A. Schammel; Eric J. Holzmueller; John W. Groninger; Charles M. Ruffner; John L. Nelson (Ecologies, 2025)
Catastrophic wind events play important but poorly documented roles in shaping bottomland hardwood forest structure and composition. The objective of this study was to survey a forested wetland area in Illinois, USA, twenty years following a severe tornado (wind speeds ranging from 333–418 km/h). Part of the damaged area had a subsequent salvage logging operation, and we compared the stand structure and composition of these damaged areas to adjacent reference sites. Stem density, basal area, and diversity differed significantly but slightly among disturbance types (p < 0.05). The density of Quercus spp. decreased in regenerated stands, while the density of Fraxinus pennsylvanica and invasive non-native species cover increased (p < 0.05). Salvage logging further increased the density of key bottomland taxa: Salix spp., Taxodium distichum, and Nyssa aquatica, as well as early successional species such as Liriodendron tulipifera (p < 0.05). Productivity did not differ between wind-impacted areas that were logged and not logged (p > 0.05). Recognizing the need for caution when informing management with case studies, this study highlights the value of delaying the assessment of even extreme wind disturbance impacts in hardwood forest recovery until the contribution of crown regrowth of severely wind-damaged trees, along with post-disturbance origin regeneration, can be ascertained.